Impact of various night-time period definitions on nocturnal ambulatory blood pressure. Issue 11 (18th November 2022) - Nolde, Janis M.; Hillis, Graham S.; Atkins, Emily; Von Huben, Amy; Marschner, Simone; Chan, Justine; Reid, Christopher M.; Nelson, Mark R.; Figtree, Gemma; Chalmers, John; Usherwood, Tim; Rodgers, Anthony; et al.
Abstract : Background: Several definitions of night-time BP exist for the calculation of nocturnal blood pressure (BP) based on 24-h BP measurements. How much these methods differ regarding the resulting nocturnal blood pressure values, under which circumstances these differences become clinically meaningful, and under which circumstances diary-adjusted measurements should be used preferentially remains uncertain. Methods: Data of 512 24-h BP recordings were analysed regarding differences in nocturnal BP based on three alternative definitions of night-time: 2300–0700 h, 0100–0500 h, and diary-adjusted measures. Results: Mean systolic nocturnal BP between 2300–0700 h was 2.5 mmHg higher than between 0100 and 0500 h and 1.6 mmHg higher than diary adjusted estimates. Up to 38.3% of individuals showed BP differences of more than 5 mmHg when comparing temporal definitions of night-time, resulting in significant proportions of individuals being re-classified as hypertensive. When diary-derived sleeping patterns differed by less than 2 h from the 2300 to 0700 h fixed time definition, mean BP discrepancies remained below 3 mmHg. Absolute time discrepancies between diary and 2300–0700 h fixed time definition of 2–4, 4–8 or at least 8 h led to SBP/DBP differences of 4.1/3.1, 6.8/6.1, and 14.5/9.1mmHg, respectively. Conclusion: Average differences of nocturnal BP between varying definitions in study/cohort data are small and would be of limited relevance in many settings. However, substantial differences can be observed in individual cases, which may affect clinical decision-making in specific patients. In patients whose sleeping patterns differs by more than 2 h from defined fixed night-times, diaries should be used for adjustment. Abstract :